2023
DOI: 10.17582/journal.jahp/2023/11.3.258.266
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility of Bacterial Organisms in Raw Fish of Pond and Retail Market

Jameel- ur-Rehman,
Asghar Ali Kamboh,
Ahmad Ali Moryani
et al.

Abstract: Current study aimed to explore the prevalence and antimicrobial susceptibility profile of bacterial organisms isolated from fish samples. A total of 120 fish samples were collected from fish retail market and ponds (60 from each source) comprising of three fish species i.e., Labeo rohita (LR; local name Rohu), Catla catla (CC; local name Thaila) and Cirrhinus mrigala (CM; local name Morakhi). The samples were processed for isolation of bacterial organisms using conventional culture method and isolates were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Information on AMR prevalence in the plant, aquaculture, and environmental sectors is relatively limited. Still, sporadic studies reported high rates of multidrug-resistant bacteria in fish [ 44 , 45 , 46 ], and consistently higher resistance rates to commonly used antibiotics in soil Pseudomonas aeruginosa isolates within 25 m of poultry farms [ 47 ]. Notably, AMR surveillance activities in different sectors were reported by the assessors as mostly operated in silos with limited cross-sectoral collaboration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on AMR prevalence in the plant, aquaculture, and environmental sectors is relatively limited. Still, sporadic studies reported high rates of multidrug-resistant bacteria in fish [ 44 , 45 , 46 ], and consistently higher resistance rates to commonly used antibiotics in soil Pseudomonas aeruginosa isolates within 25 m of poultry farms [ 47 ]. Notably, AMR surveillance activities in different sectors were reported by the assessors as mostly operated in silos with limited cross-sectoral collaboration.…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, Pakistan embarked on a national consultative process for the development of antimicrobial prescribing guidelines for livestock, although these guidelines had not been finalized by the time of the assessment. The growing aquaculture industry in Pakistan also fuels an increased reliance on antimicrobials to prevent and treat diseases [ 15 , 46 ]. National guidelines for AMU in this sector had not been developed at the time of the assessment.…”
Section: Resultsmentioning
confidence: 99%